DEKONSTRUKSI PELACUR DALAM NOVEL CHRYSAN KARYA HAPIE JOSEPH ALOYSIA - , lisa pratiwi; , Dr. Wening Udasmoro, M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research explains the deconstruction of prostituteâs discourse in novel Chrysan by Aloysia Joseph Happie. The prostitute who placed by the society as a pathology, being different displayed. Novel Chrysan presents for opposing the society normative views on prostitution. This research aims to look the Chrysanâs deconstruction at the society normative view about prostitution and hidden discourse that built Chrysan. The problems which will be answered on this research are how paradoxality in Chrysan and how the self-deconstruction on Chrysan. This research uses deconstruction approach formulated by Derrida. Deconstruction is based on basic assumption that the language is marked by instability. Signifier/text with signified/author doesnât separate. There is always a space between the signifier and signified that makes their relationship unstable. Deconstructive reading aimed at finding the failure of any text which attempt to close itself with a single meaning. To know the deconstruction in novel Chrysan, researcher uses a method of deconstruction, which identifies a hierarchy of opposition in the text so it appears which systematically privileged. The oppositions are reversed, for example by showing the interdependence between it, or to propose privilege in reverse. Third, to introduce a new term or idea that can be incorporated into the old opposition. The result of this research indicates binary opposition paradoxality, namely the ideal world and the real world. The result of the deconstruction analysis on whore showed that the main character in the novel shows the break-in of some hierarchical semantic field. The semantic field is not a whore, spiritual, family, holy, home, normal, heaven, and village. Another break-in also appears on the temporal aspect. That break-in attempt, show the textâs inconsistency. The text deconstructs itself which pull the characters in the novel back to the real world.